2018
DOI: 10.1111/jocn.14587
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of interruptions during medication administration: An integrative review of direct observational studies

Abstract: The findings from this review can be used to guide the identification and development of targeted interventions and strategies that would have the most substantial impact to reduce and manage interruptions during MA. Interruption management strategies have the potential to lead to a decrease in medication errors and an increase in task efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 38 publications
1
32
0
1
Order By: Relevance
“…31 A recent review of interruptions in the context of nursing medication administration in hospital settings concluded that interruptions are likely to occur at least once during nursing medication administration processes in hospital settings. 33 These authors recommended that individuals and organisations adopt interruption management strategies to decrease prescribing errors and increase task efficiency.…”
Section: Figurementioning
confidence: 99%
“…31 A recent review of interruptions in the context of nursing medication administration in hospital settings concluded that interruptions are likely to occur at least once during nursing medication administration processes in hospital settings. 33 These authors recommended that individuals and organisations adopt interruption management strategies to decrease prescribing errors and increase task efficiency.…”
Section: Figurementioning
confidence: 99%
“…While existing research establishes the link of interruptions encountered by nurses with subsequent MAEs (Tong et al, ), further research is required to establish this link specifically to interruptions experienced by nurses in pediatric units. As MAEs pose a serious threat to the safety of patients (Schroers, ), appropriate interventions are urgently required to decrease interruptions and thus reduce the MAE rate.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, pediatric patients are considered to be an at‐risk group in terms of medication administration (Özkan et al, ). The consequences of MAEs are including great emotional costs to error‐maker, and patients and family members lose trust in the healthcare system (Institute for Safe Medication Practices (ISMP), ; Schroers, ). While there are no studies available estimating the economic cost of MAEs in pediatric units, it is estimated that MAEs result in 21 billion dollars annually across all healthcare settings (da Silva, & Krishnamurthy, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations